2020
DOI: 10.1039/d0sm00982b
|View full text |Cite
|
Sign up to set email alerts
|

Micellar structure and transformations in sodium alkylbenzenesulfonate (NaLAS) aqueous solutions: effects of concentration, temperature, and salt

Abstract: We investigate the shape, dimensions, and transformation pathways of micelles of linear sodium alkylbenzenesulfonate (NaLAS), a common anionic surfactant, in aqueous solution. Employing Small Angle Neutron Scattering (SANS) and surface...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 64 publications
3
21
2
Order By: Relevance
“…It is used in emulsifiers, detergents, and wetting agents. The phase behavior of NaLAS in water has been characterized with respect to the different phases that form at different temperatures and concentrations. For example, Richards et al and Stewart et al studied the phase behavior of NaLAS in water. Both studies showed that at low NaLAS concentrations, a single micellar (L 1 ) phase was present.…”
Section: Introductionmentioning
confidence: 99%
“…It is used in emulsifiers, detergents, and wetting agents. The phase behavior of NaLAS in water has been characterized with respect to the different phases that form at different temperatures and concentrations. For example, Richards et al and Stewart et al studied the phase behavior of NaLAS in water. Both studies showed that at low NaLAS concentrations, a single micellar (L 1 ) phase was present.…”
Section: Introductionmentioning
confidence: 99%
“…As for NaDBS, it is known to be composed of sulfonates with different chain lengths [ 34 ]. Thus, its exact composition was determined via high-performance liquid chromatography coupled with mass spectrometry (HPLC-MS; for technical details, see below).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, a marked decrease in the surface tension as well as CMC with increasing salt concentration is observed at the presence of electrolytes at a fixed temperature [ 5 , 9 , 12 , 13 , 14 , 15 , 30 , 31 , 32 , 33 , 34 , 35 ]. For NaDBS as well as other sulfonates, this stems from (1) the reduction of repulsive forces acting between negatively charged head-groups as a result of cation–sulfonate interactions, and from (2) the decreased hydration of surfactant molecules owing to strong cation hydration, which in turn promotes hydrophobic interactions [ 14 , 15 , 31 , 34 , 35 , 36 ]. The interplay of these two effects leads to the well-known order of ‘salting-out’, observed first for proteins by Hofmeister [ 15 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…These techniques are nowadays rather robust and well developed; however, they lack sensitivity at a molecular scale to characterize the aggregates themselves. To perform this determination, one has to revert to more involved methods like X-rays and neutron scattering , or nuclear magnetic resonance (NMR) spectroscopy . Optical methods have also been proposed such as fluorescence, ,, Raman spectroscopy, resonant Rayleigh scattering, , or a nonresonant one as in dynamic light scattering or quasi elastic light scattering , as well as resonant hyper-Rayleigh scattering (HRS) and third harmonic scattering .…”
Section: Introductionmentioning
confidence: 99%